Desain Pembelajaran Menggunakan Konteks Perkembangbiakan Hewan Secara Vegetatif pada Materi Bentuk Pangkat di Sekolah Menengah Pertama - Arieyantini, Pramanika; Putri, Ratu Ilma Indra; Kesumawati, Nila (Universitas Hamzanwadi, 2017)
The research is purposed to generate aÂ learning trajectory that supports students to understand the concepts of exponential through the context vegetative propagation in animals. The Design Research was chosen as the exact method to achive the objective. Hypotetical learning trajectory in the design research played an important role as the design and research instrument. Hypotetical learning trajectory was designed as the preliminary design and was examined to 50 students from the ninth graders of YPI Tunas Bangsa Junior high school.Â (e.g 6 students from pilot experiment and 44 students from teaching experiment). The result of the learning experiment showed that drawing activity of the process of animal vegetative propagation could motivate the students to see the form of the animal multiplication. While seeing the animal multiplication through modeling (scheme, chart, and diagram), the students had an idea to calculate new animals had been formed, and used multiple numeral to determine the sum of the new animals. From the multiple numeral, an idea to state it in terms of repetitive numeral would bring the students into a definition of exponential. Based on the result above, its suggested that context containing multiplication form be used, let the students see multiplication, and the students do it mathematically into the basic concept when they are learning exponential.